Van marginaal naar mainstream? Populisme in de Nederlandse geschiedenis - Vossen, Koen (BMGN - Low Countries Historical Review, 2012)
From Marginal to Mainstream?: Populism in Dutch History In this article populism is perceived as a thin ideology with specific core concepts (a homogeneous people, a treacherous elite and popular sovereignty) that can flourish when specific conditions are met (political dissatisfaction, convergence of the established parties, increasingly opaque governance and new media). In the Netherlands one might discern three ‘populist moments’ – a period between 1916 and 1918, a period between 1963 and 1967 and a period which started in 2001/2002 and which seems not yet to be over. In electoral terms the first and second populist moments were rather weak. Both times the populist rhetoric was incorporated by (one of) the established parties. In 2001/2002 the established parties again attempted to incorporate populism but with less result. The new populism of the twenty-first century proved to be much stronger and much more durable in terms of its electoral strength and its programmatic appeal.